Optimal costs of HIV pre-exposure prophylaxis for men who have sex with men - McKenney, Jennie (PLoS One, 2017)
INTRODUCTION: Men who have sex with men (MSM) are disproportionately affected by HIV due to their increased risk of infection. Oral pre-exposure prophylaxis (PrEP) is a highly effictive HIV-prevention strategy for MSM. Despite evidence of its effectiveness, PrEP uptake in the United States has been slow, in part due to its cost. As jurisdictions and health organizations begin to think about PrEP scale-up, the high cost to society needs to be understood. METHODS: We modified a previously-described decision-analysis model to estimate the cost per quality-adjusted life-year (QALY) gained, over a 1-year duration of PrEP intervention and lifetime time horizon. Using updated parameter estimates, we calculated: 1) the cost per QALY gained, stratified over 4 strata of PrEP cost (a function of both drug cost and provider costs); and 2) PrEP drug cost per year required to fall at or under 4 cost per QALY gained thresholds. RESULTS: When PrEP drug costs were reduced by 60% (with no sexual disinhibition) to 80% (assuming 25% sexual disinhibition), PrEP was cost-effective (at <$100,000 per QALY averted) in all scenarios of base-case or better adherence, as long as the background HIV prevalence was greater than 10%. For PrEP to be cost saving at base-case adherence/efficacy levels and at a background prevalence of 20%, drug cost would need to be reduced to $8,021 per year with no disinhibition, and to $2,548 with disinhibition. CONCLUSION: Results from our analysis suggest that PrEP drug costs need to be reduced in order to be cost-effective across a range of background HIV prevalence. Moreover, our results provide guidance on the pricing of generic emtricitabine/tenofovir disoproxil fumarate, in order to provide those at high risk for HIV an affordable prevention option without financial burden on individuals or jurisdictions scaling-up coverage.